Team Work in Business Negotiations - Öberg, Britt-Marie (HERMES - Journal of Language and Communication in Business, 1993)
This is a case study of an authentic Swedish business negotiation, stretched over a time of nearly one year and divided into three sessions. The study traces and describes the phases within the negotiation process and it shows that the phase structure of each session is related to the global structure of the entire negotiation. The second part of the study concerns cooperative talk within the negotiating teams, teamtalk, and cooperative talk across the teams, grouptalk. It describes the relationship between the phases in the negotiation process and the development of different types of cooperative talk. The third part of the study indicates the relationship between the interactional character of the negotiation and the different phases. It shows how a monological interaction pattern with several instances of teamtalk in the presentation phase, gradually changes into a dialogical interaction pattern with many instances of grouptalk in the closing phase.